Implementation of Problem-Based Learning Model to Facilitate the Understanding of Information System Audit Materials - Andi Basru Wawo; Tuti Dharmawati (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to determine and improve students' understanding of the Information System Audit material using the problem-based learning model. It is hoped that this research can provide benefits for the development of effective learning models to support the formation of the personality and scientific qualities of students and improve the skills of lecturers in developing learning models. This research is a classroom action research with a problem-based learning model. The research subjects are students studying at the Accounting Study Program, Faculty of Economics, Halu Oleo University in the 2018/2019 academic year who take information systems audit courses. The results showed that implementing the problem-based learning model could improve students' understanding of the information system audit material. It can be seen through an increase in students' complete learning from before when the pre-test was 0% in a row; from each cycle, there was an increase until the post-test was 95.6%. Students' interest in inactiveness and collaboration is also good, namely 3.44 (scale 1-4). This study also found that the problem-based learning model improved students' ability to solve problems, think critically, and build their knowledge because information systems audit materials require direct skills and in-depth understanding.